1995
DOI: 10.1021/bi00042a011
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Cytochrome Oxidase with Hydrogen Peroxide: The Relationship of Compounds P and F

Abstract: Upon reaction of cytochrome oxidase with hydrogen peroxide, the spectral changes are complete, with slightly less than 1 equiv of hydrogen peroxide per cytochrome oxidase. At pH 8 the product is a mixture of the P and F forms, while at pH 6 the product is exclusively the F form. These data are inconsistent with current interpretations of the structure of compounds P and F. Two stable radical species are detected by EPR; the relative amounts of these species are pH dependent. The MCD spectra of pure P and F are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
182
5
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(209 citation statements)
references
References 30 publications
(52 reference statements)
20
182
5
2
Order By: Relevance
“…Its population increases as the pH increases in the protocol used by the present authors and by Fabian and Palmer (24,26), but not in that used by Proshlyakov et al (23). The latter authors reported that in the pH 7.4 -10 range, the population of the 607-nm form decreases at higher pH, and the final distribution of the enzyme between the 607-and 580-nm forms at a given pH depends on the enzyme preparation.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations
“…Its population increases as the pH increases in the protocol used by the present authors and by Fabian and Palmer (24,26), but not in that used by Proshlyakov et al (23). The latter authors reported that in the pH 7.4 -10 range, the population of the 607-nm form decreases at higher pH, and the final distribution of the enzyme between the 607-and 580-nm forms at a given pH depends on the enzyme preparation.…”
Section: Discussioncontrasting
confidence: 49%
“…It should be noted that Fabian and Palmer (24,25) reported the formation of 7% of a radical species in the oxidized CcO/H 2 O 2 reaction, whereas MacMillan et al (27) reported a yield of 20% for a tyrosine radical species produced in the same reaction. Interestingly, density functional calculations have shown that in the covalent bond between N ⑀ of His-276 and C ⑀ of Tyr-280, the neutral radical of the tyrosine Y ⅐ could place the spin density of N ␦ of the histidine, and thus, coupling between the copper and the organic radical, Y ⅐ -Cu(II) B 3 Y-Cu B (III) might occur (57).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The peak-to-trough magnitude of the H 2 O 2 -induced difference spectra in the Soret band was typically 30-45 mM Ϫ1 cm Ϫ1 in the WT and in the K channel mutants as compared with ca. 50 mM Ϫ1 cm Ϫ1 observed for beef heart enzyme (29,(42)(43)(44) Before the flash, the sample was incubated for several minutes with 1 mM H2O2 to convert heme a3 to the ferryl-oxo state. After recording a trace (Wildtype), 1 mM potassium cyanide was added and the second trace (ϩKCN) was recorded.…”
Section: Resultsmentioning
confidence: 99%